Twitter Sebagai Media Pemenuhan Kebutuhan Informasi Penggemar Musik Korea di Indonesia - Pasaribu, Berliana Maharani (Universitas Negeri Padang, 2022)
This study aims to describe the information needs of Korean music fans in Indonesia and to describe Twitter as a media for meeting these information needs. This research method uses descriptive research with a qualitative approach. Data collection techniques were carried out by interview, observation, and literature study. The results showed that the information provided briefly, concisely, and clearly on Twitter made the information needed by Korean music fans in Indonesia easily available. Its features and Korean music-related accounts that available on Twitter also play an important role in meeting their information needs.